Employee attitudes and work values on job performance of selected non-managerial Bangko Sentral ng Pilipinas - Iloilo Personnel. - Velarga, Marlon A (2000.)
This study sought to determine the degree of importance on work values and the relationship of employee atitudes on the job peformance of the rank-and-file personnel of the Bangko Snetral ng Pilipinas, BSP Branch - Iloilo City. It made use of 37 employees from different divisions who took the survey on employee attitudes and work values. The scores obtained from these surveys were correlated with the respondents' corresponding job performance evaluation. It utilized Pearson r method to statistically analyze employee attitudes with job performance while the data on work values were interpreted using its frequency and percentage distributions. Results showed that there was a postive correlation between employye attitudes and job performance. The outcome proved significant when it yielded a Pearson Correlation Value of 0.678 at the 0.01 alpha level (1-tailed). The performance-attitude relationship was basically validated by the Performance-Satisfaction-Effort Loop Theory, which explains that high performance always lead to high employee satisfaction and not usually the other way around. Conversely work values vary from each employee. The respondents valued highly on Service (70.3%) while they held a low importance on Variety at 29.7%.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Employees -- Bangko Sentral ng Pilipinas -- Iloilo Personnel